Return and Risk of German Open-End Real Estate Funds - Raimond Maurer; Frank Reiner; Ralph Rogalla (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2003)
Open-end real estate funds (so called “Offene Immobilienfonds”) play a major role in the German market for securitised real estate investments. Such funds are pools of money from many investors, which are invested in real estate by special investment management companies. This study seeks to identify the risk and return profile of this investment vehicle (before and after income taxes), to compare them with those of other major asset classes, and to provide implications for their appropriate role in a mixed-asset portfolio. Addition-ally, an overview of the institutional architecture and role of German open-end real estate funds is given. Empirical evidence suggests that the financial characteristics of open-end real estate funds are in many respects similar to those reported for direct real estate invest-ments. Accordingly, German open-end real estate funds qualify for medium and long-term investment horizons, rather than for shorter holding periods.
urn:nbn:de:hebis:30-17840
Keywords: 330; asset allocation; long-term investments; open-end real-estate fund; shortfall risk; Immobilienfonds; Portfolio-Management; Rendite; Rendite; Risiko; Deutschland